„Nie myśl wiele, ciskaj śmiele”. Kultura zabawy i przepowiadanie przyszłości na szlacheckim dworze w świetle sortilegium Seweryna Bączalskiego „Fortuna albo Szczęście" - Paszkiewicz, Matylda (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article provides an analysis of Fortuna albo Szczęście (Fortune or Luck) published around 1644–1646, first under the title Kształt Fortuny (Shape of Fortune) in 1609, which is an example of Polish fortune-telling book written by Seweryn Bączalski, an early-17th century author. His position in the baroque Kraków literary environment is analysed by means of Bourdieu’s theory of literary field. The textual base helps to state that Bączalski was switching between high-artistic and popular modes of writing in order to attract the readers. Fortuna… is put in the context of European and Polish tradition of lottery books and it is scrutinized in terms of its composition and two ways of its reception (as a game and as a divination tool). An analysis of the ludic representation of the goddess Fortuna and the sketch image of szlachta mentality inscribed in the texts of oracles helps to conclude that Bączalski transposed the cultural emblems to the popular horizon of thought in order to create a game that was a source of aesthetic pleasure.